Expression of SMURF family in pancreatic cancer and its effect on cell proliferation and migration - Zhang, Chen; Li, Caoyi; Wu, Long; Wang, Yuan; Huang, Ke; Yang, Xu; Zhao, Sai; Zhu, Haoran; Shi, Lin; Wang, Jian (Frontiers in Oncology, 2025)
ObjectiveThis study aims to evaluate the expression of Smad ubiquitination regulatory factors (SMURFs) in pancreatic cancer and analyze their relationship with cancer staging and prognosis, and to investigate the potential of SMURF as a therapeutic target for pancreatic cancer.MethodsA total of 179 patients with pancreatic cancer were identified in The Cancer Genome Atlas (TCGA) database. This dataset was utilized in the study to analyze the expression of SMURF1 and SMURF2 and their correlation with pancreatic cancer staging and patient survival. In vitro assays including CCK-8, EdU, colony formation, and wound-healing were employed to elucidate the function of SMURF1 in the proliferation and migration of pancreatic cancer cells.ResultsHigh expression of SMURF1 showed a significant positive correlation with T staging, histological and pathological grades, as well as clinical treatment outcomes of pancreatic cancer (P<0.050). Meanwhile, high expression of SMURF2 indicated a positive correlation with the histological grade of pancreatic cancer (P<0.050). However, high expression of SMURF1 was negatively correlated with overall survival (OS) and progression-free interval (PFI) (P<0.050). High expression of SMURF2 was negatively correlated with PFI (P<0.050). Inhibition of SMURF1 expression suppressed the proliferation and migration of pancreatic cancer cells.ConclusionHigh expression of SMURF1 could potentially be a therapeutic target and a poor prognostic indicator in pancreatic cancer.